Palimpsestos do sítio Ruínas do Teatro : perspectivas da arqueologia urbana na cidade de Laranjeiras-SE - Santos, Marcia Rodrigues (2015)
This work exposes the outcomes obtained from the research performed in the urban context ambit that focus on Urban Archaeology as a support to understand the city of Laranjeiras, Sergipe. The city here is understood from the construction of modernity based in the practices and social behavior resulting from the adoption of the bourgeois way of life. The purpose is to draw a historical-urban panorama of Laranjeiras of the nineteenth century and analyze their dynamics, under the hypothesis the local construction of modernity from representations and practices politics, economic and social of its population. Therefore, I approached about the historical site “The Ruins of the Theatre”, this local was the stage for many activities that constituted its palimpsests. The methodology applied is solidified on the theoretical reference of Urban Archaeology to interpret and contextualize the history of the building and, thereby, identify the evolution of the city of Laranjeiras and its urban development. The results allowed to build the concept of modernity from the particularities of the landed elite, of German immigrants, free workers and the large number of slaves, social agents responsible for building, spread and consolidation of ideas of modernity that desolated the Brazil at the turn of XIX century.